(untitled) (Journal of Medical & Health Sciences Review, 2025)
Oxidation in edible oil and fat is one of the main problems that fat and oil industry is facing. Due to human health concerns, synthetic antioxidants usage in food products is severely controlled. The present study was conducted to evaluate the capability of pea pod extract to prevent oxidation in sunflower oil. Pea pods were collected and sunflower oil was procured from local market. After extraction, extract was subjected to antioxidant activity analysis (FRAP assay and DPPH assay) and physicochemical analysis. Fatty acid profile of extract was determined by GC-FID. Then pea pod extract was incorporated in commercially available sunflower oil at the concentration of 600ppm, 800pp, 1000ppm and 1200ppm. During 60 days of storage all blended oil samples, were subjected to physicochemical analysis to assess the oxidative stability. During 60 days of storage FFA value increased and it ranged from 0.18±0.03 to 0.46±0.05, saponification value increase it ranged from 193.36±1.60 to 200.39±1.78. Peroxide value increased and it was within range of 1.96±0.07 to 11.44±0.95. The overall results indicate that the pea pod extract has high antioxidant activity and it has improved the oxidative stability of sunflower oil during 60 days of storage. Sensory evaluation showed that among all treatments T3 got the highest sensory attributes and was selected as best one.